Maternal heated tobacco product use during pregnancy and allergy in offspring. Issue 4 (11th October 2022) - Zaitsu, Masayoshi; Kono, Kenta; Hosokawa, Yoshihiko; Miyamoto, Manabu; Nanishi, Keiko; Okawa, Sumiyo; Niki, Shinji; Takahashi, Kyo; Yoshihara, Shigemi; Kobashi, Gen; Tabuchi, Takahiro
Abstract: Background: Little is known about the association between maternal use of heated tobacco products (HTPs) during pregnancy and the onset of allergy among offspring. This study aimed to determine whether maternal HTP smoking is associated with allergy in their offspring and to evaluate the potential dose–response association. Methods: In this web‐based, cross‐sectional survey conducted in July and August 2021 in Japan, we investigated 5688 pairs of postpartum women and infants (<3 years). Clinical diagnoses of infant asthma, rhinitis, conjunctivitis, or atopic dermatitis were reported. Using multilevel Poisson regression, we estimated the prevalence ratios (PRs) and 95% confidence intervals (CIs) of allergy in infants with HTP smoking categories cross‐classified by pregnancy periods, and adjusted for potential covariates including maternal cigarette smoking and partner's smoking status. Non‐smokers served as the reference group. Results: In total, 2.4% women smoked HTPs during pregnancy. Allergy occurred in 7.8% of the infants. The prevalence of allergy increased among the offspring of current HTP smokers during pregnancy at 15.2% (PR = 1.98, 95% CI 1.28–3.05); this association was the most pronounced during the first trimester but attenuated before pregnancy and postpartum. Dose–response associations were observed, for example a one‐unit increase in daily maternal HTP use during pregnancy was associated with a 5% increase in allergy onset. Sub‐group analyses excluding cigarette smokers during pregnancy and sensitivity analyses using the International Study of Asthma and Allergies in Childhood questionnaire showed a similar pattern. Conclusions: Maternal HTP smoking during pregnancy is associated with allergy in the offspring. Abstract : We sought to determine whether maternal HTP smoking is associated with allergy in their offspring. Overall, 2.4% women smoked HTPs during pregnancy. Allergy occurred in 7.8% of the infants. The onset of allergy increased among the infants of current HTP smokers during pregnancy at 15.2%, with a dose–response association (a 5% increase in allergy onset by one heat stick use/day).Abbreviation: HTP, heated tobacco product